2004
DOI: 10.1111/j.1440-1703.2003.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass, production and nutrient distribution of a natural oak forest in central Korea

Abstract: Biomass, production, and nutrient distribution of a pure Quercus variabilis Bl. stand (stand 1) and two mixed Q. variabilis -Q. mongolica Fisch. stands (stand 2 and 3) were investigated in central Korea. Stand 1 naturally occurred on a site with a southern aspect while stand 2 and stand 3 occurred on sites with a northern aspect. Total (overstory + understory vegetation) biomass (t ha -1 ) and annual production (t ha -1 year -1 ) were 137.8 and 11.1 for stand 1, 216.2 and 16.6 for stand 2, and 253.3 and 19.7 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 8 publications
4
24
1
2
Order By: Relevance
“…Oak forest had a vegetation C density of 35.0-37.7 t C ha −1 , which was close to the value (31.8 t C ha −1 ) for that under mid-succession in the same region [27] , but much lower than that of old-growth oak forests in the same latitude. For example, Son et al [29] reported a vegetation C density of 68.9-126.7 t C ha −1 for a natural oak forest in central Korea, which is 2-4 times of our data. Pine plantation stored 47.0-54.0 t C ha −1 in vegetation, which was higher than the mean C density of other pine forests in Dongling Mt.…”
Section: Densitiessupporting
confidence: 58%
“…Oak forest had a vegetation C density of 35.0-37.7 t C ha −1 , which was close to the value (31.8 t C ha −1 ) for that under mid-succession in the same region [27] , but much lower than that of old-growth oak forests in the same latitude. For example, Son et al [29] reported a vegetation C density of 68.9-126.7 t C ha −1 for a natural oak forest in central Korea, which is 2-4 times of our data. Pine plantation stored 47.0-54.0 t C ha −1 in vegetation, which was higher than the mean C density of other pine forests in Dongling Mt.…”
Section: Densitiessupporting
confidence: 58%
“…However, below-ground biomass constituted only 6-8% of the total biomass for humid tropical secondary forest in Mexico (Hughes et al 1999). In a Korean oak forest, below-ground biomass constituted 11% of the total biomass (Son et al 2004). This difference may result from site condition (particularly water availability and soil fertility) and different species characteristic of evergreen forest zones (Hughes et al 2000).…”
Section: Biomass Accumulationmentioning
confidence: 97%
“…The most common approach to obtaining biomass estimates at stand level is by use of regression equations that are fitted to morphometric measurements taken from destructive sampling of individual trees. In the past several decades, many allometric equations have been developed for different tree species worldwide (Cannell 1982;Feng et al 1999;Jaramillo et al 2003;Tanabe et al 2003;Son et al 2004). However, above-ground biomass varies with species, site quality, climate, stand age, and density (Cannell 1982;Bråhen and Hagberg 2004).…”
Section: Introductionmentioning
confidence: 99%
“…mongolica and Q. variabilis are two of the most common oak species that are widely found in natural deciduous and mixed forests throughout Korea (Yi 2003, Son et al 2004a, 2007a, Park et al 2005a, Kwon and Lee 2006b) and play an important role in ecological, social and economic aspects in terms of increased biodiversity, cultural significance, and wood production across the country. Over the past several decades, data sets on biomass and productivity of Q. mongolica and Q. variabilis forests have been published with the large accumulation of field survey data (Song et al 1997, 2005a, Son et al 2004b). Son et al (2005) first calculated and tested the values of root to shoot ratio (R) and BEF for Q. mongolica and Q. variabilis by age classes using e destructive method.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of Q. mongolica or Q. variabilis forest stands from most of the previous studies indicated the overstory vegetation was relatively or purely dominated by Q. mongolica or Q. variabilis, and little biomass information on other overstory species was reported (Song et al 1997, 2005a, Son et al 2004b). Thus, we assumed that the overstory vegetation was purely dominated by Q. mongolica or Q. variabilis in the reported oak forests.…”
Section: Biomass Conversion and Expansionmentioning
confidence: 99%